The impact of vehicle movement on exploitation parameters of roads and runways: a short review of the special issue - Dell’Acqua, Gianluca; De Luca, Mario; Prato, Carlo G.; Prentkovskis, Olegas; Junevičius, Raimundas (Transport, 2016)
„The impact of vehicle movement on exploitation parameters of roads and runways: a short review of the special issue" Transport, 31(2), p. 127-132 First published online: 30 May 2016